Os espaços não formais de ensino e as práticas de educação ambiental nas escolas municipais de Cachoeiro de Itapemirim-ES - Puppim, Regina Rosa (2023)
The act of learning can take place in any space, whether it is formal or non-formal. The aim is for education to go beyond the walls of the classroom, beyond the walls and grids of schools, seeking contributions from Non-Formal Education Spaces (ENFE) to Environmental Education (EE) practices. In order to give students at municipal schools in Cachoeiro de Itapemirim-ES, a better understanding of the place where they live, they need to develop a critical environmental awareness, through contact with the ENFE practices that exist in the city. The research approached teachers about the socio-environmental impacts of the marble and granite production chain, going beyond simply observing the company in the city's landscape, and also understanding the environmental impacts caused. The research took place in the school environment with the teachers. It is a qualitative case study, with data collection instruments such as: direct observation, field diary, interviews and questionnaires, to find out if they receive continuing education on the subject of environmental education? Do they know what an ENFE is? After collecting the data, content analysis was used according to Bardin (1977). As a result, the teachers show that they have a humanist view of environmental education, they understand critical environmental education as a way of life, the use of marble quarries as ENFEs still does not happen frequently, even though they are spaces full of potential and can be accessed by the teachers surveyed in the municipal schools of Cachoeiro de Itapemirim-ES